Insulin-like growth factor II prevents apoptosis in a human teratoma derived cell line. Issue 3 (June 1995) - Granerus, M; Bierke, P; Zumkeller, W; Smith, J; Engström, W; Schofield, P N
Abstract : Aim —To study how insulin-like growth factor II (IGF-II) affects the behaviour of human teratoma cells. Methods —The human pluripotential teratoma cell line Tera 2 was cultured under serum-free conditions in the presence or absence of IGF-II. Effects on cell proliferation and apoptosis as well as on the expression of the proto-oncogene c- myc were studied. Results —In this study we show that Tera 2 cells deprived of serum undergo programmed cell death (apoptosis). The onset of nuclear fragmentation was observed 12 hours after serum withdrawal. The morphological changes of the Tera 2 cell nuclei were confirmed by the occurrence of a nucleosome ladder. However, the constitutive expression of the proto-oncogene c- myc was not decreased in parallel with initiation of apoptosis. The apoptotic response to serum withdrawal could be counteracted by simultaneous addition of IGF-II. In addition it was found that human testicular tumours (seminoma and embryonal carcinoma) contain raised levels of insulin-like growth factors. Conclusions —The precise roles of IGF-I and IGF-II have been unclear, and there is overwhelming evidence against these factors as primarily transforming agents. The finding that IGF-II apparently counteracts apoptosis in vitro may well explain its effects on tumours in vivo.